2022
DOI: 10.1186/s12883-022-02969-8
|View full text |Cite|
|
Sign up to set email alerts
|

Increased neutrophil-to-lymphocyte ratio is associated with unfavorable functional outcomes in acute pontine infarction

Abstract: Background The neutrophil-to-lymphocyte ratio (NLR) is positively associated with unfavorable outcomes in patients with cerebral infarction. This study aimed to investigate the relationship between the NLR and the short-term clinical outcome of acute pontine infarction. Methods Patients with acute pontine infarction were consecutively included. Clinical and laboratory data were collected. All patients were followed up at 3 months using modified Ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Following publication of the original article [ 1 ], the authors reported an error in the author group. Author Zongyou Li is one of the two corresponding authors of the article.…”
mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported an error in the author group. Author Zongyou Li is one of the two corresponding authors of the article.…”
mentioning
confidence: 99%